Effects of physical exercise on mental health and general self-efficacy of city residents in COVID-19 - Jianyu Jia; Li Song; Lin Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The purpose of this study was to investigate the relationship and impact of residents' self-efficacy and mental health in the context of COVID-19. A quantitative research approach is used in this study. This study investigated residents with a general self-efficacy questionnaire to explore the predictive effect of self-efficacy on mental health. Therefore, a questionnaires survey is employed in this study to collect primary data. While data collection, the cross-sectional research design was used, and data analysis was carried out using a statistical tool. There was a significant negative association between the epidemic's risk perception and the score of the SCL.90. The standardized burden of understanding the epidemic on its latent variables was more than 0.65 in the measurement model, indicating that the 90 percent confidence intervals for the three mediation paths did not include 0, confirming the mediation effect's establishment. This study reveals the relationship between self-efficacy and mental health and its mechanism of action, inspiring the maintenance of residents' mental health during the period of the new crown. It is concluded that there was a significant positive correlation between self-efficacy and understanding of the epidemic situation.